Eksposisi Kata dan Frasa Pelayanan Sosial Politik Nabi Samuel di Masa Pemerintahan Transisi - Yonathan Mujianto (IMMANUEL: Jurnal Teologi dan Pendidikan Kristen, 2021)
The phrase that "Samuel ruled as judge over the Israelites all his life" indicates that the spiritual and governmental responsibilities did not cease until he died. The atmosphere of socio-political service is described even more strikingly and impressively when the monarchy reigned under the reign of the first king in Israel under the reign of King Saul. Socio-political service does not stop even though he is no longer the leader of the Israeli people, namely as a judge, but he still interacts with socio-political issues in addition to the spiritual and social problems of his nation. This fact of Samuel's ministry shows the need for a realistic understanding in today's society that the leadership of God's people in this matter can also be the leadership of God's church so as not to refuse at all or be hesitant to take part in ministry in socio-political life. In this paper the author only examines the exposition of words and phrases, namely trying to understand the knowledge or understanding of the biblical texts which are clearly closely related to the socio-political ministry of the Prophet Samuel so that this knowledge can be appropriated so that God's people can apply them in socio-political life. present time. The research method used in this paper is descriptive method. The use of this descriptive method is used to get a clear picture of the exposition texts, whether they are phrases / phrases or words that intersect with the experience and ministry of the prophet Samuel in the socio-political field during the transition period from the rule of judges to the monarchy of Israel. The themes of the descriptive study and discussion are formed from the exposition of the phrases and words in the socio-political field of the ministry and experience of the prophet Samuel.AbstrakFrasa bahwa “Samuel memerintah sebagai hakim atas orang Israel seumur hidupnya” mengindikasikan bahwa tanggungjawab spiritualitas dan pemerintahan tidak terhenti sampai dia meninggal. Suasana pelayanan sosial-politik justru terdeskripsikan dengan lebih mencolok dan mengesankan ketika pemerintahan monarkhi di bawah pemerintahan raja pertama di Israel di bawah pemerintahan raja Saul. Pelayanan sosial-politik tidak berhenti meskipun bukan lagi menjadi pemimpin umat Israel, yaitu sebagai hakim tetapi dia tetap berinteraksi dengan masalah-masalah sosial-politik di samping masalah spiritual dan sosial bangsanya. Fakta pelayanan Samuel ini menunjukkan perlunya pemahaman secara realistis dalam kehidupan bermasyarakat pada masa kini bahwa pimpinan umat Tuhan dalam hal ini bisa juga pimpinan gereja Tuhan agar tidak menolak sama sekali atau gamang untuk mengambil bagian pelayanan dalam kehidupan sosial-politik. Dalam tulisan ini penulis hanya mengkaji secara eksposisi atas kata dan frasa yaitu berusaha memahami pengetahuan atau pemahaman dari teks-teks Alkitab yang jelas erat berkaitan dengan pelayanan sosial-politik Nabi Samuel agar kemudian pengetahuan tersebut dapat diapropriasikan agar dapat diaplikasikan umat Tuhan dalam kehidupan sosial-politik masa kini. Metode penelitian yang digunakan dalam tulisan ini adalah metode deskriptif.  Penggunaan metode deskriptif ini digunakan untuk mendapatkan gambaran yang jelas atas teks-teks eksposisi baik itu frasa/ungkapan atau kata yang bersinggungan dengan pengalaman dan pelayanan nabi Samuel dalam bidang sosial-politik di masa-masa transisi dari pemerintahan para hakim menjadi pemerintahan monarkhi Israel.  Tema-tema kajian dan pembahasan yang deskriptif tersebut terbentuk dari eksposisi atas frasa dan kata bidang sosial-politik dari pelayanan dan pengalaman nabi Samuel.